THE IMPLEMENTATION OF CURRICULUM 2013 FOR TEACHING AND LEARNING ENGLISH AT THE TENTH GRADE STUDENTS OF MA NEGERI TARAKAN IN ACADEMICYEARS 2018/2019 - Imran Bin Ali; Ridwan Ridwan (Edukasia : Jurnal Pendidikan, 2019)
The research design of this research was case study. The research objects of this research were the English teacher at the tenth grade and the head master of MA Negeri Tarakan. The technique of collecting data in this research used three instruments there were: observation sheet, interview, and document analysis. The result of this research is curriculum 2013 in MA Negeri Tarakan has already implemented but not running well. The implementation of curriculum 2013 only 60 percent that implement in the class; the English teacher need to understand the authentic assessment and all of items in scientific approach. In conducting teaching and learning process the English teacher could teach based on lesson plan but it was not effective. Then, the problems that the English teacher faced in implementation of curriculum 2013 in teaching preparation mostly in preparing media that would be use in teaching process because lack of facility in the classroom, in making written preparation especially on lesson plan the English teacher need to make the appropriate indicator with the syllabus because the indicator is very important to measure the students’ ability. In teaching and learning process the teacher have some problems: lack of training until the teacher couldn’t apply the scientific approach, couldn’t manage the class well, lack of media in the classroom because the English teacher just prepare the media in language laboratory. In teaching evaluation the teacher couldn’t apply scientific approach well it made the teacher couldn’t use the authentic assessment because lack of training in curriculum 2013